(untitled) (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2025)
This study assesses whether sectoral infrastructure spending in West Papua effectively improves human development outcomes aligned with the regional goals of Healthy Papua, Smart Papua, and Productive Papua. Using balanced panel data from 13 districts and cities between 2021 and 2024, the analysis applies fixed effects and dynamic GMM estimators to capture both contemporaneous and lagged effects of infrastructure investment in economic, education, and health sectors. The findings reveal that economic infrastructure spending consistently produces the strongest and most immediate impact, significantly increasing GRDP per capita and confirming the infrastructure-led growth hypothesis. Health infrastructure investment also demonstrates dual benefits, contributing directly to higher life expectancy and indirectly to economic expansion. In contrast, education infrastructure spending significantly improves average years of schooling but shows no short-term effect on economic performance, highlighting the long-run nature of educational returns. The study further identifies strong regional fixed effects and meaningful annual shocks, indicating that structural differences and national policy cycles shape development trajectories. Overall, the results underscore the need for more targeted, long-term, and sector-integrated infrastructure strategies to achieve equitable and sustainable human development in geographically complex regions such as West Papua.